Prenatal Care in Pregnancies Through Assisted Reproductive Technologies (ARTs): A Narrative Review Article - Fahimeh Ranjbar; Zahra Behboodi Moghadam; Maryam Gharacheh (Iran University of Medical Sciences, 2017)
Background: Understanding the physiological and psycho-social effects of pregnancy through Assisted Reproductive Technologies (ARTs) will enable health care providers to identify and treat any adverse outcomes, and provide support to women seeking fertility treatments. The aim of this paper was to review studies describing prenatal care in pregnancy through ARTs. Methods: A systematic search of the electronic databases including Medline/Pubmed, ISI Web of science and EMbase, persian databases and Google Scholar search engine was performed with keywords 'assisted reproductive technology', 'in vitro fertilization', 'prenatal care', 'midwifery' and 'pregnancy'. Qualitative, quantitative and review studies in English and Persian languages, published between 1990-2017 were selected, and 51 papers related to prenatal care in assisted pregnancies (In Vitro Fertilization (IVF) and Intra Cytoplasmic Injection (ISCI)) that met the inclusion criteria were reviewed. Results: The important issues regarding the prenatal care for women who conceive through ARTs include gaining the mother's trust, involving the spouse in prenatal care, taking an accurate history, considering the underlying cause of infertility and the history of treatment, understanding theadverse consequences of ARTs on the health of the mother and fetus, helping the mother adapt to pregnancy and develop an attachment to the fetus, managing ARTs-related psychosocial issues, and maintaining confidentiality. Conclusion: Midwives managing the assisted pregnancies should be well aware of the unavoidable effects of ARTs on pregnancy to provide appropriate prenatal care.